Pencegahan dan Pemulihan Remaja Kecanduan Game Online - Andi Prasasti Saputra; Ivan Pratama Saputra; Hengki Wijaya (Ra'ah: Journal of Sociology of Religion, 2023)
In the era of the industrial revolution 4.0, technology is increasingly experiencing rapid development. Online games are one result of these technological developments. Every age without exception has been touched by this modern technology, especially teenagers. Addiction is not inevitable. The rise of the evolution of online games in this day and age, makes more and more teenagers experience addiction. Therefore, the purpose of this study is to find out what are the causes and effects of online game addiction, find out what preventive measures can be taken to prevent addiction in adolescents and finally find out what recovery measures can be taken to recover adolescents who have experienced addiction game online. The research method used in this research is descriptive qualitative by collecting references through literature studies so as to produce several explanations which are discussed systematically. The results of this study indicate that there are so many factors that cause adolescents to experience online game addiction and in the process of prevention and recovery the role of parents is needed, as well as involving God in the process.